EFL Students’ Perceptions of Learning Experiences Using the Inquiry Method: A Survey Study - Neni Kustina Sari; Aprilia Yunda Supasa (International Journal of Pedagogy, 2024)
This study aims to find out how EFL students perceive their learning experience using the inquiry method at Lancang Kuning University. This quantitative study was survey-based in its design. The study employed convenience sampling as a technique of data collection. It was discovered that four elements reflected this survey: critical discourse, authentic investigation, experience-based hypothesis, and conclusion-based transfer. Students' perceptions are merely "Moderate" (Mean= 3.81 and SD=0.84) according to the study's findings on four different criteria. In conclusion, Inquiry-based learning encourages students to actively investigate and learn, leading to a deeper understanding of the subject matter. Students learn to analyze, evaluate, and draw conclusions from information, fostering critical thinking abilities. Students gain valuable skills like initiative, self-direction, and communication, applicable beyond the classroom